2019
DOI: 10.1210/clinem/dgz078
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Metastatic Patterns Between Subtypes of Thyroid Carcinoma Results From the Nationwide Dutch Pathology Registry

Abstract: Background Metastatic disease is the main cause of cancer-related mortality in thyroid carcinoma (TC) patients. Clinical studies have suggested differences in metastatic patterns between the different subtypes of TC. This study systematically evaluates the metastatic patterns of different subtypes in TC patients. Methods A nationwide review of pathological records of all 650 patients diagnosed with a primary malignancy in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 28 publications
3
21
0
Order By: Relevance
“…Although reports of patients experiencing more than three metastatic sites are scarce, Hugen et al . reported that over 60% of all patients with metastasized DTC have multiple metastases, corroborating our findings [ 19 ]. However, this was an autopsy study, and some of the included patients were not diagnosed with a thyroid malignancy during their lifetime, limiting the applicability of these results.…”
Section: Discussionsupporting
confidence: 92%
“…Although reports of patients experiencing more than three metastatic sites are scarce, Hugen et al . reported that over 60% of all patients with metastasized DTC have multiple metastases, corroborating our findings [ 19 ]. However, this was an autopsy study, and some of the included patients were not diagnosed with a thyroid malignancy during their lifetime, limiting the applicability of these results.…”
Section: Discussionsupporting
confidence: 92%
“…Thyroid cancer (TC) is a common thyroid malignant tumor, including papillary TC, follicular TC, anaplastic TC and medullary TC. 1 Papillary TC is a more common type of TC, which has a lower degree of malignancy and a better prognosis. 2 In recent years, the incidence of TC has increased significantly, which is related to the region, race and gender.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is slower typically for well-differentiated thyroid cancers and faster for poorly differentiated or anaplastic thyroid cancers. This high frequency of silent metastases is supported by the aforementioned autopsy series in which 15.6% of the 359 patients diagnosed with thyroid cancer incidentally at autopsy also had distant metastases [10]. Thus, in thyroid cancer, it seems likely that the majority of "recurrence" at distant sites represents growth of preexisting metastases occurring as early stage events that are biologically dormant (i.e.…”
Section: Recurrent Vs Residual Thyroid Cancermentioning
confidence: 87%
“…This "seed and soil" relationship for cancer metastasis, where the location of metastatic progression has tissue specificity, was suggested more than a century ago by Paget [7][8][9]. In thyroid cancer, the specificity of location of metastases for the different thyroid cancer subtypes was affirmed in a recent 25 year autopsy study that included more than 650 cases from the Netherlands [10]. Additionally, primary cancers are now recognized to be comprised from a non-uniform heterogeneous group of cancer cells along with stromal and immune cells that can both constrain and promote progression depending on their cell type [11].…”
Section: Introductionmentioning
confidence: 95%